Characterization of ionospheric mapping function at equatorial region / Mohd. Zaffan Mohd. Zaini - Mohd. Zaini, Mohd. Zaffan
The parameter of ionosphere that contributes severe effects on radio signals is the total number of electron content or total electron content (TEC). TEC can be estimated from the code and phase measurements based on the extracted Global Positioning System (GPS) data. Information of TEC reflects the relationship to the ionospheric layers due to high density of electron concentration at F region. At equatorial region (geographical latitude: 25° S to 25° N), the peak electron density height region varies from 275 km to 575 km and varies marginally from 3(1(1 km to 350 km at and beyond the anomaly crest region. It is vital to use suitable mapping function at equatorial region so that TEC value can be obtained precisely. The equatorial's ionosphere is unique due to the exposure of ultraviolet (UV) radiation from the sun at this region is much higher. This paper clarify the characterization of TEC mapping based on Single Layer Model (SLM) and Modified Single Layer Model (M-SLM) in order to determine the appropriate TEC value in equatorial region. TEC is extracted using R1NEX format GPS dual frequency data that supplied by JUPEM (Department Of Survey and Mapping Malaysia). This paper investigates the TEC parameter covered the period of 4 hours duration (day and night) on 8 November 2005 from two different GPS receiver stations, located at Wisma Tanah Kuala Lumpur, KTPK and at Universiti Sains Malaysia, USMP.